Psychometric properties of the Iranian version of the Sexual Modes Questionnaire (SMQ): to assess the association between automatic thoughts, emotions and sexual response. Issue 1 (2nd January 2017) - Abdolmanafi, Atefe; Azadfallah, Parviz; Fata, Ladan; Winter, Sam; Farahani, Hojatollah; Peixoto, Maria Manuela; Nobre, Pedro
ABSTRACT: The role of cognitive-affective factors on male and female sexual functioning has been studied in North America and European countries and there is a lack of validated measures available for use elsewhere. The aim of this study was to translate and validate the Sexual Modes Questionnaire (SMQ) to the Iranian context. The SMQ is a validated measure aimed at assessing the association between thoughts, emotions and sexual response during sexual activity. A total of 388 participants (224 women and 164 men) completed the SMQ. A principal component analysis with varimax rotation and subsequent confirmatory factor analysis (CFA) were performed. Three factors were identified in the male version: Failure Anticipation Thoughts, Erection Concern Thoughts, and Lack of Erotic Thoughts. In the female version, six factors were identified: Failure and Disengagement Thoughts, Low Self-Body Image Thoughts, Sexual Abuse Thoughts, Sexual Passivity and Control, Lack of Erotic Thoughts, and Partner's Lack of Affection. Also, a consistent pattern of correlations was found between the three subscales of the SMQ (thoughts, emotions, and sexual response) supporting the interactional character of the measure. This study has provided some preliminary evidence of the reliability and validity of the SMQ for use in Iranian populations.